The atherogenic lipoprotein subfraction studies in patients with familial hypercholesterolaemia - Raao, Frederick Johan (My University, 2014)
Familial hypercholesterolaeinia (FH) is an inherited disorder caused by mutations in th e low-density lipoprotein (LDL) receptor which lead to diminished clearance of cholesterol from the circulation and, consequently, to markedly elevated LDL-cholesterol (LDL-C) levels. The resultant hypercholesterolaem ia predisposes these patients to severe prem ature atherosclerosis, particularly coronary artery d isease (CAD). T he concentration of LDL-C and lifetime vascular exposure to raised plasm a LDL-C concentrations are major determ inants of atherosclerosis, but there rem ains a considerable variability in the extent of atherosclerosis presen t and in the expression of clinical disease in these patients. Qualitative differences in LDL such a s LDL particle size and susceptibility to lipid oxidation may play a role, as may other biochemical risk factors. The purpose of this thesis was to determine whether such qualitative differences in LDL are important determinants of the extent and severity of atherosclerosis and to determine whether it is mainly the reduction in LDL-C that is of benefit, or whether antioxidant therapy would also be effective in preventing progression of atherosclerosis in FH subjects. FH patients were found to have large, buoyant LDL particles, which are less susceptible to lipid oxidation than smaller, d en ser particles. In the absence of other causes of insulin resistance, patients with FH have normal fasting insulin and triglyceride levels, normal postprandial lipaemia, and do not have microalbuminuria. They, therefore usually show no features of the metabolic syndrome despite severe, accelerated atherosclerosis. Similarly, the role of lipid oxidation in the pathogenesis of atherosclerosis in FH remains uncertain. LDL isolated from FH patients is more resistant to oxidation, and antioxidant therapy appears to be of little or no benefit in preventing progression of atherosclerosis in these hypercholesterolaem subjects. Particularly in severely hypercholesterolaem ic subjects, m ore conclusive proof of a protective effect of antioxidants from large prospective studies presently in progress is needed before antioxidant therapy can be advocated for the treatm ent and prevention of atherosclerosis. In subjects with FH, quantitative rather than qualitative differences in LDL are associated with accelerated atherosclerosis. Therapy in FH should therefore be aimed primarily at reducing LDL-C levels.